Directive Speech Acts: a Cross-Cultural Study - Chubaryan, Astghik; Sargsyan, Lilit (Armenian Folia Anglistika, 2011)
Linguistic communication is one of the underlying ways of human interaction. Every day we carry out numerous speech acts trying to interpret others’ speech acts in an attempt to find out whether they suggest, advise, warn or threaten something. Things get more complicated when we deal with people representing other cultures. Particularly in the 21st century when we witness and participate in expansion of intercultural relations in the process of globalization, the role of intercultural pragmatics gets more important. Thus, our investigation is another attempt to compare directive speech acts in the context of the norms of Anglo-Saxon and Armenian cultures. The results of our research give us a chance to claim that the differences of the aforementioned speech acts in Armenian and English are conditioned by different attitudes towards the cultural values rooted deep in the given linguoculture.